2007
DOI: 10.1073/pnas.0705888104
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis for passive immunotherapy of Alzheimer's disease

Abstract: Amyloid aggregates of the amyloid-␤ (A␤) peptide are implicated in the pathology of Alzheimer's disease. Anti-A␤ monoclonal antibodies (mAbs) have been shown to reduce amyloid plaques in vitro and in animal studies. Consequently, passive immunization is being considered for treating Alzheimer's, and anti-A␤ mAbs are now in phase II trials. We report the isolation of two mAbs (PFA1 and PFA2) that recognize A␤ monomers, protofibrils, and fibrils and the structures of their antigen binding fragments (Fabs) in com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
136
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(142 citation statements)
references
References 40 publications
6
136
0
Order By: Relevance
“…Atomic resolution structures have been reported for microcrystals of short amyloid fragments only (Sawaya et al, 2007). Crystallographic studies of A␤ complexed/fused with other proteins include the following: (1) IDE (insulin-degrading enzyme) in complex with A␤ 40 (Shen et al, 2006), in which only A␤ residues 1-3 and 16 -23 were observed; (2) the immunodominant B-cell epitope of the A␤ 1-8 fragment in complex with murine antibodies, which revealed extended coil-like conformations of the epitope (Gardberg et al, 2007;Miles et al, 2008); and (3) the A␤ 28 -42 fragment fused with the C terminus of ribonuclease Tk-RNase HII, which illustrated a limited ␤-conformation (Takano et al, 2006). Nuclear magnetic resonance (NMR) data interpretations of fibrils formed from different A␤ peptides infer either parallel or antiparallel orientations of the ␤-sheets (Lynn and Meredith, 2000;Egnaczyk et al, 2001;Tycko, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Atomic resolution structures have been reported for microcrystals of short amyloid fragments only (Sawaya et al, 2007). Crystallographic studies of A␤ complexed/fused with other proteins include the following: (1) IDE (insulin-degrading enzyme) in complex with A␤ 40 (Shen et al, 2006), in which only A␤ residues 1-3 and 16 -23 were observed; (2) the immunodominant B-cell epitope of the A␤ 1-8 fragment in complex with murine antibodies, which revealed extended coil-like conformations of the epitope (Gardberg et al, 2007;Miles et al, 2008); and (3) the A␤ 28 -42 fragment fused with the C terminus of ribonuclease Tk-RNase HII, which illustrated a limited ␤-conformation (Takano et al, 2006). Nuclear magnetic resonance (NMR) data interpretations of fibrils formed from different A␤ peptides infer either parallel or antiparallel orientations of the ␤-sheets (Lynn and Meredith, 2000;Egnaczyk et al, 2001;Tycko, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Recognition of the hydrophobic central part is also a strategy pursued in the search for peptide or peptidomimetic inhibitors of A␤ fibrillation (15)(16)(17). Recently, the structures of the antigen binding fragments of two antibodies to the N-terminal A␤ (1)(2)(3)(4)(5)(6)(7)(8) peptide were reported (18). However, the structural basis of interactions with the central and C-terminal parts of A␤ remains elusive.…”
mentioning
confidence: 99%
“…A second generation of candidate therapeutics has included a series of attempts to inhibit the formation of amyloid plaques. Active (16)(17)(18)(19)(20)(21)(22)(23) and passive (24) immunization approaches are presently being tested. However, some patients in the active human immunization trials have developed meningoencephalitis (25,26).…”
mentioning
confidence: 99%